Clinical and pathological differences between the pyogenic granuloma and lobular capillary hemangioma in the oral cavity: a scoping review - Ver Berne, Jonas; J. Raubenheimer, Erich; Jacobs, Reinhilde; Politis, Constantinus (Journal of Stomatology, 2020)
Since initially described, the terms “pyogenic granuloma” (PG) and “lobular capillary hemangioma” (LCH) have undergone a significant change in meaning, which leads to a confusion in the literature. In this study, we attempted to investigate if there are any clinical and pathological differences between the pyogenic granuloma and lobular capillary hemangioma through a scoping review of the available literature. A Medline search has identified 342 articles from 2001 to 2018, from which English papers, case series, retrospective studies, and cross-sectional studies were selected. Data from the articles was charted using appropriate subheadings for the clinical question (e.g., number of patients, clinical features, histology, pathogenesis, differential diagnosis, treatment). Compared to LCH, PG seems to occur more in the middle-aged range, has a clearer predilection for (pregnant) females, and has more frequently a known triggering factor in the history. Histologically, PGs appear as radially organized capillaries (while LCHs have a lobular pattern), have a mixed inflammatory infiltrate (compared to the occasional lymphocytic infiltrate in LCHs), and can undergo fibrosing transformation when chronic, which is not seen in LCHs. Finally, besides basic excision, several other treatment options have been described for both lesions. Since the pyogenic granuloma and lobular capillary hemangioma show clinical and pathological differences, we propose them to be considered as distinct lesions, which makes interpreting the literature much easier.